Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Pada Sugest Kopi Keude Matangglumpangdua - Nora, Yeni Safitri; Rini, Endang Sulistya; Fadli, Fadli (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
This research aims to examine the analysis of marketing strategies to increase sales on Sugest Kopi Keude Matangglumpangdua. Research methods with qualitative methods are based on the philosophy of postpositivism with a descriptive qualitative approach. The research took place at Sugest Kopi Keude Matangglumpangdua, Peusangan District, Bireuen Regency which was carried out from July 2021 to September 2021. Sugest Kopi is a café. The data type is primary data and secondary data. Data collection techniques include observation, documentation, and interviews. As for the data analysis technique with SWOT analysis. The results showed an average score of internal strategy factor scores of 7,69. This means that the internal strategy factor is in the strong and high category, which is already very good in terms of strengths and or weaknesses in the Sugest Kopi business opportunity. The average score of the external strategy factor score was 9,12. This means that the external strategy factor is in the strong and high category, which is already very good in terms of opportunities and or threats of business opportunities in Sugest Kopi. Sugest Kopi  also needs to increase the number of supporting facilities to attract consumers to return to buy and visit by providing seats to lean on. Of course, free Wifi is provided to consumers.